Analysis of the Effect of Exercise Therapy on Reducing Pain in Patients with Type 2 Diabetes Mellitus Who Have Diabetic Ulcers - Handariati, Atik; Salihun, Saleha; Maulida, Gina Rizkyani; Putra Mardiansyah, Muhammad Faizal (Rifa'Institute, 2025)
Introduction: Pain in patients with type 2 diabetes mellitus who develop diabetic foot ulcers substantially impairs mobility, wound management, and quality of life, and effective non-pharmacological strategies are urgently needed. Objective: This study aimed to analyze the effect of an exercise therapy program on pain reduction in patients with type 2 diabetes mellitus with diabetic foot ulcers. Method: A randomized controlled trial was conducted involving 60 patients selected by consecutive sampling and allocated to an exercise group (n = 30) or control group (n = 30). The exercise group received an eight-week structured foot and ankle exercise program three times per week in addition to standard care, while the control group received standard care only. Pain intensity was measured using a 0–10 cm visual analogue scale before and after the intervention. Result and Discussion: Baseline pain scores were comparable between groups (6.83 ± 1.21 versus 6.77 ± 1.18). Post-intervention, mean pain decreased to 3.41 ± 1.52 in the exercise group and 5.93 ± 1.44 in the control group. Mean change in pain was −3.42 ± 1.37 versus −0.84 ± 1.10, respectively (t = 7.97; p < 0.001; standardized effect size = 1.99), indicating a large and clinically meaningful effect. Conclusions: Structured exercise therapy significantly reduces pain in patients with type 2 diabetes mellitus with diabetic foot ulcers and should be considered as an adjunct to standard ulcer management.